Lowe Syndrome: A Complex Clinical Diagnosis with a Novel Mutation in the OCRL Gene - Parikh, Akanksha C.; Gadgil, Pradnya (Journal of Child Science, 2021)
Lowe syndrome (LS) is a rare X-linked condition having a clinical triad of congenital cataracts, intellectual disability, and progressive tubular nephropathy. Although the easily recognizable symptom complex usually evolves by infancy, a unifying diagnosis is often missed. We present a young boy with a prolonged history of multisystem affection, finally leading to the clinical suspicion of LS. The diagnosis was confirmed on genetic analysis as well as a previously unreported mutation in the OCRL gene was discovered. A 9-year-old boy with intellectual disability and recent onset seizures was referred for the evaluation of rickets. In addition, there was a significant past history of neonatal cataracts, infantile glaucoma, persistent albuminuria, and severe short stature with growth hormone deficiency. The characteristic involvement of eyes, brain, and kidneys along with a family history of a maternal uncle being similarly affected led to the clinical suspicion of LS. A whole exome sequencing was performed, which not only confirmed a nonsense mutation, c.2530C > T, in exon 23 of the Lowe gene (OCRL) but also revealed it to be a novel pathogenic variant. This case highlights the importance of piecing together the different facets of a complex clinical syndrome in reaching a challenging diagnosis. Also, LS must be kept as a differential in any child with neonatal cataracts and intellectual disability. Genetic confirmation of LS in our patient partly relieved the parental anxiety, and the child continued to remain under follow-up with multiple specialists, only now with a definite diagnosis.
Keywords: oculocerebrorenal syndrome; rickets; growth hormone deficiency; nonsense mutation